DEKONSTRUKSI PERAN GENDER DALAM NOVEL RE: DAN PEREMPUAN KARYA MAMAN SUHERMAN - Zulfikar, Muhammad Nizar; Qomariyah, U'um (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research aims to uncover the forms of deconstruction of gender roles and the search for women's existential freedom in the novel Re: and peRempuan by Maman Suherman through Simone de Beauvoir's existentialist feminist approach and deconstruction theory. Using a qualitative method with a descriptive-analytical approach through a close reading technique on data in the form of narratives and dialogues representing women's positions, roles, and consciousness in patriarchal systems. This research aims to uncover how Re: and peRempuan display, critique, and/or redesign gender roles, both at the level of discourse and subjective experience. The results of the study show that the novels Re: and peRempuan not only depict women's suffering in a patriarchal social system, but also present a form of resistance and identity negotiation carried out by women. Maman Suherman deconstructs binary oppositions such as holy and unclean and feminine to show that these meanings are unstable.